Rolex: Watches / Muhammad Irfan Suhaimi ... [et al.] - Suhaimi, Muhammad Irfan; Izzuddin, Muhammad Syahrul; Mohd Ramli, Maisarah Alia; Azman, Nur Fatin 'Aqilah; Mohamad Hashim, Nurkamalia Natasha (2018)
The company major strength is their product quality. Mostly, the company have the high quality to keep stay along and not easy to break down. The weakness of the company is about their cost that is too expensive. Next, the opportunity of the company benefit from acquiring additional established luxury brands and lastly, the threat of the company is mobile phones acting as substitutes of the watches. To conclude this executive summary, SWOT analysis helps a companies to figure out any problems and try to find the solution to improve. So the companies can reduce the weakness and increase the strength of the product that made by the companies. We also made some improvement and recommendation.